Construction of Z-scheme Ag/In2S3/ZnO nanorods composite photocatalysts for degradation of 4-nitrophenol. (16th December 2020) - Wei, Junwei; Wei, Shuoming; Chang, Na; Wang, Haitao; Zhang, Jimei
Abstract: Herein, Ag/In2 S3 /ZnO nanorods (NRs) composite photocatalysts were successfully prepared via simple methods. Significantly, hydroxyl radical active substances were found in the electron spin resonance tests of In2 S3 /ZnO NRs and Ag/In2 S3 /ZnO NRs, which indicates that the oxidation reaction that oxidizes water or hydroxide ions into hydroxyl radicals occurs on the valence band of ZnO NRs. It suggests that Z-scheme heterojunction was successfully constructed. In the photocatalytic experiments of degrading 4-nitrophenol (PNP), the Ag/In2 S3 /ZnO NRs composite exhibits higher photocatalytic activity than ZnO NRs, In2 S3, Ag/ZnO NRs and In2 S3 /ZnO NRs. The characteristic peak of PNP disappears completely in 50 min. The enhanced photocatalytic performance can be attributed to the formation of Z-scheme heterojunction between ZnO NRs and In2 S3 . In addition, local surface plasmon resonance of Ag and Schottky junction formed between Ag and In2 S3 also promote the photocatalytic activity.